ผลการใช้ EC-CAR Model ในการอบรมปฏิบัติการ การจัดทํางานวิจัยปฏิบัติการในชั้นเรียนตามวงos P-A-O-R ของครูโรงเรียนกีฬา สถาบันการพลศึกษา : กระทรวงการท่องเที่ยวและกีฬา - Suksinai, Direk (Academic Journal of Thailand National Sports University, 2022)
The purposes of this research were to study the results of EC-CAR Model in workshop for performing classroom action research (CAR) as the followings: 1) problems and method for solving students' problems using in classroom action research (CAR) of sport school teachers, 2) study teachers' knowledge and quality in CAR according to P-A-O-R cycle, and compare teachers' CAR knowledge before and after participated the workshop, 3) compare teachers' knowledge and quality in CAR across personal factors, and 4) indicate influences in EC-CAR model of 4 activities on CAR knowledge and CAR quality. Populations were 119 teachers of sport schools under Physical Education Institute, Ministry of Tourism and Sport who participated workshop between May 7-9, 2011 at Wasitti Hotel, Suphanburi. Research instruments were coding manual and coding form for CAR synthesis, test of CAR knowledge, questionnaires, and CAR evaluation form. yzed by percentage, mean, standard deviation, t-test, one way ANOVA, and content analysis. The results showed that: 1) most problems found in CAR were skills and abilities, methods most used for solving problems were extra practicing, and most of teachers succeeded in solving students' problems, 2) teachers' level of CAR knowledge and CAR quality were moderate, and teachers' CAR knowledge higher than before workshop, 3) CAR knowledge and quality were different across age, number of teaching class, educational level, position, teachers' learning area, geological region, and 4) activities in EC-CAR model which influenced on CAR knowledge and CAR quality was coaching activities.